2020
DOI: 10.4162/nrp.2020.14.6.637
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption frequency of Korean adults based on whether or not having chewing difficulty using 2013–2016 KNHANES by sex-stratified comparative analysis

Abstract: BACKGROUND/OBJECTIVES: This study examined the associations between food consumption frequency of Korean adults and self-perceived chewing difficulty, using the food frequency questionnaire (FFQ, 112 items) from 2013-2016 of the Korea National Health and Nutrition Examination Survey (KNHANES). SUBJECTS/METHODS: Subjects were divided into not difficult in chewing (NDC) and difficult in chewing (DC) groups, with 24.17% being classified into DC. Males and females consumed 35 and 37 items less frequently than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(If you use dentures, please indicate the discomfort experienced when chewing while wearing them)." Responses of "very uncomfortable" and "uncomfortable" were considered as the presence of chewing difficulty, whereas responses of "moderate", "not uncomfortable", and "not uncomfortable at all" were considered as its absence [38]. In addition, we defined tooth loss/chewing difficulty as present if an individual had at least one of these conditions.…”
Section: Number Of Teeth and Chewing Abilitymentioning
confidence: 99%
“…(If you use dentures, please indicate the discomfort experienced when chewing while wearing them)." Responses of "very uncomfortable" and "uncomfortable" were considered as the presence of chewing difficulty, whereas responses of "moderate", "not uncomfortable", and "not uncomfortable at all" were considered as its absence [38]. In addition, we defined tooth loss/chewing difficulty as present if an individual had at least one of these conditions.…”
Section: Number Of Teeth and Chewing Abilitymentioning
confidence: 99%
“…Previous studies have shown that people with reduced oral function tend to avoid foods that are difficult to chew and are, thus, more susceptible to malnutrition [6]. It has also been reported that as oral function declines, opportunities for exercise decrease [7].…”
Section: Introductionmentioning
confidence: 99%